2010
DOI: 10.1590/s0103-90162010000300006
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the ultrastructure of soybean cultivars in response to manganese supply in solution culture

Abstract: The deleterious effects of Mn stress on many species have been studied, mainly concerning biochemical, physiological and growth parameters of plants. However, there are few studies relating the anatomical and ultrastructural changes in response to manganese (Mn) nutritional disorders, This study examined the leaf ultrastructure of Mn-inefficient (IAC-15, Santa Rosa) and Mn-efficient (IAC-Foscarin 31) soybean (Glycine max L.) genotypes in response to three rates of Mn (0.5, 2 and 200 μmol L -1 ) in the nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
1
14
0
2
Order By: Relevance
“…1). The contents of Mn detected in the present study (60 to 190 mg kg −1 DW) are comparable to those reported by Hannam and Ohki (1988) and Lavras-Junior et al (2010); these Mn contents were established to represent the optimal growth conditions of different soybean cultivars. The dose-response curve of MnDFB showed the highest SOD activity and Mn contents in the leaves of plants treated with 8 μM MnDFB ( Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1). The contents of Mn detected in the present study (60 to 190 mg kg −1 DW) are comparable to those reported by Hannam and Ohki (1988) and Lavras-Junior et al (2010); these Mn contents were established to represent the optimal growth conditions of different soybean cultivars. The dose-response curve of MnDFB showed the highest SOD activity and Mn contents in the leaves of plants treated with 8 μM MnDFB ( Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The roots and leaves were dried in an oven (70°C), ground, weighed, and digested with a nitric-perchloric acid solution (4:1) at 210°C (Lavras-Junior et al 2010). The solutions were filtered through Millex GV 0.22-μm pore PVDF membranes.…”
Section: Metal Level Measurementsmentioning
confidence: 99%
“…Excessive concentrations of Mn in plant tissues may alter various processes, such as enzymatic activity, uptake, redistribution, and the use of other nutrients (Ca, Fe, Mg, N and P), in addition to the productive responses of agricultural crops (Lavres Junior et al, 2010). The literature has reported that toxicity by metals e e.g., Mn e induces oxidative stress .…”
Section: Introductionmentioning
confidence: 99%
“…El encalado es una práctica agrícola importante en suelos ácidos para neutralizar la acidez (Castro & Munevar, 2013); en ese sentido, la adición de cal sube el pH, mejora la absorción y redistribución de N en la planta (Lavres et al, 2010) y libera el fósforo retenido en el suelo (Fisher, Yarwood, & James, 2017;Zhu, Li, & Whelan, 2018). Del mismo modo, Rosas, Puentes y Menjivar (2017) encontraron que el incremento de pH mejora la disponibilidad de P en suelos cacaoteros; por otra parte, Baligar y Fageria (2005) demostraron que el encalado mejora la disponibilidad y absorción de nutrientes en plántulas de cacao, indicando que no solo regula la fitotoxicidad sino también el uso eficiente de nutrientes (uen), ya que los suelos ácidos limitan la eficiencia de los fertilizantes, tal y como lo sugieren López, Urbina, Reynoso y Martínez (2018).…”
Section: Introductionunclassified